Hubungan Antara Motivasi Belajar Dengan Hasil Belajar Pada Pembelajaran Tematik Di Kelas V SDN Gugus III Kota Bengkulu - Cintia Fraditha; Pebrian Tarmizi (Universitas Bengkulu, 2023)
This study aims to determine the relationship between learning motivation and student learning outcomes in thematic learning in class V SD cluster III City of Bengkulu. This study uses a quantitative approach to the type of correlational. The population in Bengkulu City Elementary School III, namely SDN 17 Bengkulu City, 48 SDN Bengkulu City, Bengkulu City SDN 57, Bengkulu City SDN 03, and SDN 25, with a total of 189 students. Using sample selection guidelines according to Arikunto's opinion: if the subjects are less than 100 people should be taken altogether, if the subject is large or more than 100 people can be taken 10-15% or 20-25%, then the sample in this study was taken 25% randomly ( random) of the entire population. The sample in this study amounted to 47 students from all students in Elementary School III Bengkulu City. Research methods using questionnaire and documentation. All instruments meet the requirements as a measurement requirement, because they have been tested so that they meet the product moment T-test requirements with a significance level of 5%. The instrument used in this study was a questionnaire (questionnaire) of motivation and documentation of the repeat scores of 1 thematic learning theme for the fifth grade elementary school cluster III Bengkulu City. Data analysis techniques are used to find validity, reliability, and test the correlation coefficient.